INTERGRATION OF ASWAJA TEACHING: CONCEPT OF STRENGTHENING CHARACTER EDUCATION IN COLLEGE - Fitria Martanti (Pascasarjana Universitas Wahid hasyim Semarang, 2020)
Abstract Planting of character education must be carried out continuously. The characters that have been planted in school must be strengthened in college. The planting of character education must be taught, familiarized, trained consistently, become character and become a culture, so that the planting of education is not only in school, but must be strengthened into a culture in college. Strengthening the character in college should be more endeavored to make students who are faithful, pious, noble, moral, ethical and civilized based on the nation's noble values of religion, Pancasila, the Constitution of 1945 and the culture of moderating Islamic values. The noble values of the nation from religion and the culture of Islamic values of moderation can be seen from the Aswaja teachings that can be embedded in the teachings that can strengthen character education in universities. This research is a qualitative research conducted at Wahid Hasyim University, Semarang, which is one of the universities that base Aswaja as a foundation for strengthening character education. The source of the data is obtained from primary and secondary data. Data collection method is done by interview, documentation and observation, while data analysis method uses descriptive analysis method. The results of the study show that the concept of aswaja teaching at Wahid Hasyim University is used as the foundation that underlies all activities carried out on campus, both matters relating to aqidah, worship/sharia, and morals. As for strengthening character education through Aswaja teachings, it was carried out by making Aswaja Center which regulates activities related to Aswaja. The implementation of the Aswaja teachings is carried out through habituation, guidance and consultation related to religious practices. Aswaja's teachings are also integrated in courses according to each faculty. Key Words : Aswaja, Education, Character.